Relación entre el Deterioro Cognitivo y la Enfermedad Renal Crónica. Hospital Regional de Moquegua. Junio – Agosto del 2019. - Condori Monroy, Jonathan German (2021)
Objective: To demonstrate the relationship between cognitive impairment and chronic renal disease at the Regional Hospital of Moquegua. June - August 2019. Material and methods: According to the execution of the researcher it is an observational, prospective, transversal and analytical study of a population conformed by 75 patients with the diagnosis of chronic renal disease that fulfilled the selection criteria, data from clinical histories and the data collection sheet previously elaborated for the cognitive evaluation were obtained, for the obtaining of the results the Pearson's Chi2 test was performed. Results: Of the 75 patients, the degree of chronic renal disease affected in 54% the cognitive deterioration of the patients, the personal aspects indicate us that the affected age is from 45 years with a (NS=0.01), the time of disease with a (NS=0. 01) as for the laboratory evaluation it was observed that patients with an altered hemoglobin level with (NS=0.05), urea concentration with (NS=0.02), creatinine concentration with (NS=0.01), presented greater cognitive impairment. Conclusions: It is concluded that the degree of chronic renal disease, the chronological age of the patient, the time of chronic renal disease, the concentration of hemoglobin, urea and creatinine significantly affect the cognitive impairment of patients with chronic renal disease.